Hybrid RZF precoding algorithm for mmWave massive MIMO system - Bin XIE; Shumin XIE; Shurui LIU (Dianxin kexue)
The high cost of system and high power consumption of the traditional full digital precoding in mmWave massive MIMO systems was studied, which caused by a large number of radio frequency (RF) chain. A scheme with hybrid precoder at base station and analog combiner at user terminal was proposed. Based on the consideration of the channel characteristic, the analog precoding vectors and analog combining vectors were designed according to the antenna array response vectors of transmitting and receiving ends,respectively.Then a low dimension digital precoding was used to eliminate the influence of system noise and inter-user interference on the basis of the effective channel matrix.Simulation results show that,on the basis of effectively reducing the number of RF chain required by the system, the proposed hybrid precoding algorithm approach the performance of the full digital precoding.